Comprehensive Analysis of MeGRAS Family Genes in Cassava and their Genome Collinearity Relationship with Arabidopsis and Populus Genome - Muthusamy, Senthilkumar K; A. T., Amina; Hegde, Vivek; N., Krishna Radhika; A. V. V., Koundinya; C., Visalakashi Chandra; M. N., Sheela (JOURNAL OF ROOT CROPS, 2020)
GRAS transcription factor family genes play diverse role in plant growth and development and often have a role as integrators of multiple development regulatory and environmental signals. Functional characterization and understanding of GRAS transcription factor family genes will help to breed, high yielding improved cassava genotypes. In this study, a genome wide analysis led to identification of 78 MeGRAS genes in cassava. The genes are distributed in all the chromosomes of cassava except chromosome no. 16. The identified cassava MeGRAS family members localized in different subcellular compartments including the nucleus, cytoplasm, chloroplast and mitochondria suggest a wider cellular localization and diverse role of MeGRAS family members in cassava. Occurrence of tissue-specific (biotic, abiotic, light-responsive, circadian and cell cycle-responsive) /cis-regulatory elements in the promoter regions of the MeGRAS family showed the potential role of MeGRAS family in plant growth, plant development and stress tolerance in cassava. Genome collinearity analysis with Arabidopsis and Populus genome showed the evolution of the MeGRAS family members through duplication and divergence in cassava. This comprehensive analysis contributes for a better understanding of the complexity of MeGRAS family members in cassava, and also provide further basis to dissect their potential role in development and stress response of cassava